Institutional pressures, CEOs' attributes, and strategic response towards climate change mitigation: The case of energy firms - Jamaliah Abdul Majid; Norbaya Ab Rahim; Razita Razak (Cogent Business & Management, 2023)
This study examines strategic response towards climate change mitigation by listed firms in the energy sector in Malaysia from 2010 to 2019. It also examines whether institutional pressures and attributes of the Chief Executive Officer (CEO) drive such strategic response. Using a TwoStep cluster analysis, and based on 271 firm-year observations, the results show that there are two types of strategic response portrayed by the energy firms, i.e. indifferent and emerging. To analyze the determinants of the firms' strategic response, two logistic regression techniques are employed, i.e. robust standard errors clustered by firms and lagged structure approach. The results suggest that firms strategic response is shaped by institutional pressures and CEOs attributes, namely, CEOs with international experiences, and CEOs who have experiences in addressing environmental issues. These inferences are robust to several sensitivity tests, including the lagged structure approach, Heckman's (1979) selection bias correction, an alternative measure of firms' strategic responses, a matched-sample approach, and controlling for possible international pressures faced by the firms. Overall, the results indicate that in emerging countries, such as Malaysia, with weak pressures from non-governmental organizations, both the government and CEOs need to play dominant roles in addressing climate change issue.
Keywords: 650; CEO attributes; CEO experiences; CEO knowledge; climate change; energy sector; GHG emissions; Institutional pressures; Malaysia